Working Capital as a Mediator of Financial Distress - Gregorius Rahadian; Hadi Cahyadi; Ronnie Resdianto Masman; Estralita Trisnawati; Henryanto Wijaya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines financial distress in Indonesia Stock Exchange-listed family-owned textile and garment enterprises from 2019 to 2024. It uses working capital to mediate financial crisis and its causes. The study explores how operating cash flows, GDP, asset tangibility, leverage, and interest rate affect financial distress, employing working capital as a mediator. Panel data regression analysis utilizing SmartPLS software is used on 18 purposive-sampled organizations. The quantitative study is supplemented with an online interview with a leading Indonesian textile firm's finance director. Operating cash flow negatively impacts financial distress, asset tangibility positively impacts financial distress, while impacts negatively working capital. Financial distress is positively impacted by working capital. When mediated by working capital, operating cash flow, GDP, leverage, and interest rates have little impact on financial distress. Financial distress in family-owned textile and garment enterprises which addressed by the study, helping stakeholders to make educated choices.